Pollution sources and water quality assessment in Metro Manila and Laguna Lake Basins - Peralta, Genandrialene L. (Philippine Engineering Journal)
As one of the major tasks in the IDRC-funded project "Water Resources Management Model for Metro Manila," the water quality of both surface and groundwater resources in the Metro Manila and Laguna Lake Basins was assessed based on available data and information. Refuse dumpsites, industies and underground storage tanks as possible pollution sources were identified and map located. Groundwater quality data provided by the Metropolitan Waterworks and Sewerage Systems (MWSS) and the Department of Health (DOH) was evaluated and compared with the National Standards for Drinking Water. Groundwater quality maps for Metro Manila were generated for the following parameters : pH, chloride, turbidity, total dissolved solids, iron and hardness. A groundwater vulnerability map was developed for Metro Manila based on mappable hydrogeological parameters. Report findings on the water quality status of the Laguna Lake and Metro Manila Rivers is also presented.